Problems of Harmonizing Investment Property Accounting Аccording to Russian and International Standards - T. U. Druzhilovskaya; E. S. Druzhilovskaya (Учёт. Анализ. Аудит)
The purpose of this article is to study the problems of convergence of investment property accounting in Russian and international financial reporting standards. The relevance of the question is due to the increasing role of such objects in the activities of Russian organizations. The research methodology includes the critical analysis of regulating modern investment property accounting in Russian and international financial reporting standards. This article uses such methods as analysis and synthesis, comparison, method of analogies, method of groupings, systems approach and logical approach. The study reveals discrepancies in the conceptual apparatus connected to investment property accounting; in various Russian regulatory documents; in interpretation of the notion of investment property in Russian GAAP and IFRS along with the differences in the investment property valuation methodology in Russian and international fi reporting standards.This article investigated the regulation of all Russian and International financial reporting standards subsystems. Russian accounting standards subsystems are the regulatory documents of organizations belonging to public and private sectors. The latter includes the normative documents of financial and nonfinancial organizations. When analyzing the regulatory documents on accounting in financial organizations the documents of credit and non-credit institutions were considered separately. As international standards subsystems were considered International Public Sector Accounting Standards (IPSAS) and International Financial Reporting Standards for private sector. The authors give the critical analysis of the validity of the investment property accounting regulations in Russian and international financial reporting standards. The authors substantiate the prospects of the further convergence of the investment property accounting rules in Russian and international financial reporting standards.